Analisis Materi Graph Pada Buku Teks Pengantar Teori dan Algoritma Graph - Laila Hayati (Beta: Jurnal Tadris Matematika, 2011)
Textbooks or teaching book used in learning and teaching should have special standard that have been achieved, namely standard of material, standard of presentation and standard of language and legibility. The result of analysis has been worked, in the book of ”Pengantar Teori dan Algoritma Graph” indicates that still be gotten some definition that needs to make more clear; and in the book is not be written standard of competition, basic competition, and whatever the focus that must be achieved by the students. Based on the result of analysis, it should be used the other textbooks in learning teaching for the comparisons in understanding the concept completely; so that the students can be saved from misconception and doing something wrong systematically